THE POTENTIAL OF CELL-FREE DNA METHYLATION BIOMARKER AS AN EARLY DETECTION FOR LUNG CANCER - Muhammad Yusuf; Nasim Amar; Shintya Octaviana Baliulina (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Lung cancer is still the leading cause of cancer deaths. Current screening methods still have many limitations in diagnosing lung cancer, thus a more precise and applicable screening method is needed in diagnosing individuals with lung cancer. One of the screening methods that has the potential to help diagnose lung cancer is DNA methylation which is thought to have an advantage as a biomarker in lung cancer. Method: This literature review was conducted by including validated studies extracted through PubMed, ScienceDirect, and Cochrane Library databases. A total of 13 studies fulfilled the inclusion criteria. Discussion: DNA methylation could occur in the early stages of cancer development and was specific to different tumor types. In lung cancer, DNA methyltransferase (DNMT) regulation and ten-eleven translocation (TET) enzymes were disrupted resulting in tumor suppressor gene inactivation and cancer development. Overall, DNA methylation in the genes HOXD10 / PAX9 / PTPRN2 / STAG3, SHOX2 / PTGER4 / FOXL2, SOX17 / TAC1 / HOXA7 / CDO1 / HOXA9 / ZFP42, and CDO1 / SOX17 / HOXA7 had a sensitivity above 90%. Several other DNA methylation panels such as DCC, TMEM196, SHOX2 / PTGER4, and CDO1 / SOX17 / HOXA7 had a high specificity of up to 90-100%. AUC scores were above 0.80 in the majority of studies. DNA methylation as a support for screening methods could increase the effectiveness of early detection and reduce the rate of false positives. Conclusion: DNA methylation biomarker is an effective method for an early detection of lung cancer.